Two new species of Vanilla (Orchidaceae) in the Brazilian Atlantic Forest - Fraga, Claudio Nicoletti De; Couto, Dayvid Rodrigues; Pansarin, Emerson Ricardo (Phytotaxa, 2017)
Two new species of Vanilla are described and illustrated based on specimens collected in mesophytic semideciduous forests of southeastern Brazil. Vanilla capixaba occurs in southeastern of Espírito Santo and Vanilla paulista occurs in São Paulo. Both species are closely related to members of the Vanilla planifolia group, V. cristagalli, V. dubia and V. dungsii.